PEMENUHAN DAN DAMPAK KEBUTUHAN TOKOH UTAMA DALAM NOVEL HOLD ON ITS HURT KARYA NOVENI ADELIA - Paseru, Melisa; Juanda, Juanda; Jahrir, Andi Sahtiani (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2024)
This study aims to analyze the fulfillment of needs in an arranged marriage using the theory of humanistic psychology according to Abraham Maslow. This research is a descriptive qualitative research. The data and data source of this research is the novel Hold On, Its Hurt by Noveni Adelia published in 2023. The data collection technique is reading and note taking technique. In qualitative research, describing the data analysis process starts from data identification, data classification, to drawing conclusions as the final result. The results of this study indicate that there is a fulfillment of needs which include physiological needs, the need for security, the need for love and belonging, the need for self-esteem and self-actualization in the main character is well fulfilled, both from his social relationships and from himself even though at the beginning of marriage it is not maximized.